An essay on the new frontiers for facilities management: conceptual insights - Quinello, Robson (2022)
Purpose – Facilities Management - FM, has been the subject of international analysis and research, mainly over the last five decades, from the perspective of its contribution to the operational efficiencies of organizations. Considered a support area for operations, it is responsible for the physical infrastructure of the building and, consequently, the quality of the environment for their users. Note that in recent years the area has changed given the externalities that are discussed throughout the essay.Design/methodology/approach – The theoretical essay is based on a literature review of landmark studies that point out new externalities on the subject in the practical and theoretical field.Findings – New exogenous demands shape FM, making it an integrating and political agent for private and public physical infrastructure through the introduction of the concepts of ESG - Environmental, Social and Governance, urbanism, smart cities connected to building infrastructures, industry 4.0 and its applications, the development of ISO standards, the advancement from operational positions to strategic levels and the reconfiguration of workspaces resulting from the impact of a pandemic.Research, Practical & Social implications – The essay sheds light on the need for changes in the field of management, as well as the need for new and more in-depth studies in the academic field on the factors mentioned, which not only impact the individuals in a company, but also the community from a political perspective.Originality/value – Few studies in the field of Operations deal with FM. This essay brings interdisciplinary and contemporary aspects to both areas of knowledge.Keywords: Integrated Facility Management, Externalities, Political Entity, Political Competences.